EFFECTIVENESS OF SINGLE SESSION OF BAND LIGATION IN ACHIEVING HEMOSTASIS IN PATIENTS PRESENTED WITH ACUTE UPPER GASTROINTESTINAL BLEEDING SECONDARY TO ESOPHAGEAL VARICES - Khan, Fahim Ullah; Hassan, Muhammad Kamran; Masood, Abbas; Sohail, Muhammad (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the effectiveness of single session of band ligation in patients who had esophageal variceal bleeding. Methodology: It was a retrospective analysis of the data in which we reviewed medical records of 823 cirrhotic patients who presented with active esophageal variceal bleeding between 01/09/2015 and 31/08/2016 in Lady Reading Hospital Peshawar and assessed them for eventual outcomes i.e. initial hemostasis, rebleeding and mortality rate. Results: The mean age was 51 ±11.9 years and 523 (63.5%) were males in our study. Majority (n=603, 80.6%) belonged to Child class "C". A single session of band ligation was successful in securing hemostasis in 804 (97.67%) patients. Conclusion: Single session of band ligation was successful in achieving and maintaining hemostasis in most of the patients admitted with esophageal variceal bleed.